1980
DOI: 10.1159/000170857
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Capacity, Residual Abnormalities and Activity Habits following Total Correction for Tetralogy of Fallot

Abstract: The maximal oxygen consumption (VO2 max) of 68 patients, at a mean of 5.6 years after total correction for tetralogy of Fallot, was lower than that of normal subjects (36.3 ± 7.5 and 43.1 ± 9.0 ml/kg-min). At the time of treadmill evaluation only the female patients were less active in daily life than the normals. Patients having had an elevated right ventricle to pulmonary artery resting systolic pressure gradient, evaluated at a mean of 2.2 years after surgery, had lower VO2 max than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…These patients were selected from all patients with repaired TOF who had undergone exercise testing at our institution. Patients were included in the study if they met the following criteria: (1) they had undergone complete repair of TOF using a transannular patch with complete resection of the pulmonary valve; (2) they had a residual outflow gradient of <25 mmHg as assessed by echocardiography; (3) patients were taking no medication at the time of exercise testing; (4) no patient had a pacemaker at the time of exercise testing; (5) patients performed an exercise test to maximum aerobic capacity as measured by criteria outlined below.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…These patients were selected from all patients with repaired TOF who had undergone exercise testing at our institution. Patients were included in the study if they met the following criteria: (1) they had undergone complete repair of TOF using a transannular patch with complete resection of the pulmonary valve; (2) they had a residual outflow gradient of <25 mmHg as assessed by echocardiography; (3) patients were taking no medication at the time of exercise testing; (4) no patient had a pacemaker at the time of exercise testing; (5) patients performed an exercise test to maximum aerobic capacity as measured by criteria outlined below.…”
Section: Study Populationmentioning
confidence: 99%
“…tients with repaired TOF have mild to moderate reduction in aerobic capacity, although individual variations are large [2,4,7,9,12,16,17].…”
mentioning
confidence: 99%
“…It was found that hemodynamically significant lesions such as pulmonary stenosis or pulmonary insufficiency can result in reduced exercise capacity [29,37]. Patients after tetralogy of Fallot (TOF) repair with significant residual pulmonary stenosis had lower maximal oxygen consumption than patients with lesser residual gradients [26]. In addition, it had been shown that cardiorespiratory fitness normalized after pulmonary valve replacement in children and adolescents with repaired TOF with pulmonary regurgitation [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, Rocchini et al [15] have reported that low exercise capacity is noted in postoperative TF patients regardless of the presence or absence of pulmonary regurgitation. Hemodynamic factors, such as a diminished cardiac output [4,7,12], elevated right ventricular systolic [3,4,9] and enddiastolic [3,4,9,10] pressures, a decrease maximal heart rate [4-6, 11, 12, 14, 16-18], and abnormal distribution of lung perfusion [19] have also all been [6,7,16] have also reported that improved exercise performance has been associated with earlier primary repair. The relationship between the age at operation and functional capacity has been weil described by Wessel et al [5].…”
Section: Discussionmentioning
confidence: 99%
“…Lambert et al [6] have speculated that decreased physical working capacity in female patients is probably due to restricted physical activity. Mocellin et al [7] demonstrated that only about half of their patients took part in school sports despite permission to engage in normal physical activities.…”
Section: Discussionmentioning
confidence: 99%